Ibogaine’s potential role in supporting reward system recovery across diagnostic boundaries - Nicolas, Mark (Frontiers in Pharmacology, 2025)
This article proposes that ibogaine’s induction of GDNF, modulation of glutamate and dopamine signaling, and reopening of plasticity represent a unified mechanism capable of restoring reward system fidelity across disorders. This includes addiction, obsessive-compulsive disorder (OCD), post-traumatic stress disorder (PTSD), and eating disorders, amongst others. These conditions are labelled as distinct and separate yet share disrupted dopaminergic and glutamatergic signaling within the mesocorticolimbic circuitry as a common underlying dysfunction, resulting in maladaptive reinforcement and motivational dysregulation. Ibogaine, a little-known indole alkaloid derived from Tabernanthe iboga, has shown distinct neurobiological effects that seem to restore normal reward processing through glial cell line-derived neurotrophic factor (GDNF) upregulation, receptor modulation, and enhanced neuroplasticity. Historical, preclinical, and observational evidence suggests that ibogaine’s mechanism of action is consistent with an action on underlying reward system dysfunction rather than only on surface symptoms. However, there are some safety concerns. Ibogaine causes hERG channel inhibition, so the therapy requires adherence to strict medical protocols. This review hypothesizes that ibogaine’s neurotrophic and receptor-modulating properties act as a unifying mechanism for restoring reward-system function across diagnostic boundaries. Unlike prior ibogaine reviews that focus on addiction, this paper integrates findings across trauma, compulsive behavior, and affective disorders through the common lens of reward-circuit dysfunction. The mechanisms described here support a theoretical framework that requires empirical validation, and the predictions derived from this model are outlined within the paper.